What Are the Demotivating Factors Affecting Young Korean EFL Students? - Grace, Daniel Patrick (2018)
Demotivation is not a well-researched area in foreign language learning compared to the extensive research on motivation. Motivation and how much a learner has is very important in determining the success a language learner will have. This paper looks more into the language learners’ lack of motivation, the demotivated learner, and what are the causes for loss of motivations? We reviewed many previous studies dealing with demotivation and English language learners. This study specifically looks at young (elementary & middle school) Korean EFL (English as a Foreign Language) learners and what factors they find demotivating with their English learning experiences in public and private education. Modified from Sakai and Kikuchi’s (2009) questionnaire, a 28-item questionnaire testing 6 identified demotivating factors from the academic literature were tested on 221 young Korean EFL learners in South Korea. Generally, the results showed participants to be mostly positive with their English learning experiences. However, (Characteristics of Classes) was identified as the most demotivating factor for the study participants. Results also showed other interesting findings in terms of the compared answers between the genders and ages of the participants, as well as the positive findings detected from the questionnaire.